Siding with the Enemy: Reluctant Mobilization and the Colonial Anxiety, the Netherlands Indies in the Brink of the Japanese Invasion - Uji Nugroho Winardi (Lembaran Sejarah, 2012)
After the Netherlands was occupied by the Germany NAZI, the Dutch colonial state in the Indies was reaching to the edge of the Pacific War. To deal with the situation, the colonial government endeavored many attempts to boost the defense of the colonial state especially by advancing up their army’s weaponry and mobilizing manpower. Although gained robust support to modernize the weapons, the government only had a little success to infuse manpower to their forces. This article mainly discusses the considerations within the circle of the colonial government in order to improve the defense of the Netherlands Indies. It seeks to the answer for the question on why the colonial government’s plan to mobilize manpower only met few successes. It eventually argues that the anxiety and the attitude of the colonial government impeded their own plan to improve the defense.